Implementasi Metode Decision Tree Klasifikasi Data Mining Untuk Prediksi Peminatan Jurusan Robotika oleh Mahasiswa - Mugi Raharjo; Ridwan ridwan; Jordy Lasmana Putra; Tommi Alfian Armawan Sandi (Universitas Bina Sarana Informatika, 2019)
Specialization of majors in a study program becomes something important must be an option for a student, for that they must think carefully before choosing the majors. Because later this thing can determine the success or failure of a student to understand what they learned to apply to during the final project. In the past few years there has been a question about the problem of electing majors in the Computer Technology Study Program. Because almost every year the majority of interest voters in majors are interested in computer network majors rather than robotics majors. majoring in majors, so the authors analyzed and retrieved data from 145 student samples in the electronic practicum course and chose 7 attributes in this study because this course was very influential on the interest in the robotics department in the Computer Technology study program. The author uses the classification tree Decision method to predict interest in students. Therefore, with this research, the authors hope that in the future with the results of this analysis can be found a solution to the problem of why students are more inclined to choose the interests of departments other than robotics, whether due to factors or other factors. Keywords: Computer Technology, Analysis, Classification